On the genera Selwynia Borradaile, 1903, and Gandoa Kammerer, 2006, with descriptions of two new species from Papua New Guinea and French Polynesia (Crustacea: Decapoda: Brachyura: Aphanodactylidae) - Ng, Peter K. L.; Rahayu, Dwi Listyo (Zootaxa, 2016)
The taxonomy of the Indo-West Pacific aphanodactylid crabs Selwynia sibogae (Tesch, 1918) and S. edmondsoni (Rathbun, 1932) is discussed on the basis of the types, and both species are redescribed and figured. Two new species from Papua New Guinea and French Polynesia respectively, are described and compared with congeners. All are symbionts in polychaete tubes. A key to the genus Selwynia is also provided. The poorly known genus Gandoa Kammerer, 2006, is redescribed on the basis of the rediscovered the type species, Voeltzkowia zanzibarensis Lenz, 1905. The lectotype female of Pinnixa brevipes H. Milne Edwards, 1853, is examined and shown to be a senior subjective synonym of G. zanzibarensis.